ALEXITIMIA E MASCULINIDADES: DO SILÊNCIO AOS PROCESSOS DE DESCONSTRUÇÃO - Rosostolato, Breno (2019)
Abstract: Men grew up listening to violent expressions such as 'be strong', 'do not be a little girl', 'man doesn’t cry'. Violence in the form of ideas; concepts that formed a whole mentality, the macho culture. This is the scenario that persists in society: a wrong way of how men should be. Men who build themselves through the denial of feelings. The denial of all that is not considered "supposedly" masculine results in violence to the feminine in order to maintain virility and the social pattern of masculinity. The "mythology" behind these masculinities is the male, molded into a toxic stereotype, which produces erroneous, inappropriate, and aggressive postures. The male, for example, believes that he can’t dismiss any woman, that he must always be ready for sex or that everything must be solved with brutality. Power, control and property are hegemonic aspects that make up a place occupied by men, but, in reality, reveal another reality, of sadness, loneliness, abandonment and fear. Although the male ideal is still pursued by most men, the deconstruction of this type of masculinity is already underway, with the consequent male scene leaving. Is in this context that we present the concept of Alexithymia, that is, the difficulty in recognizing feelings; and we will do this by studying the studies of hegemonic and toxic masculinities. Keywords: alexithymia; masculinities; hegemonies; toxicity.